Stained glass windows depicting themes from Christianity - Mumbai Archive Project Team (Jio Institute, 2024)
Saint Anne’s Church features stained glass windows depicting prominent themes from Christianity. The central window depicts the Ascension of Jesus, the window on the right shows the Descent of the Holy Spirit, and the one on the left depicts the Coronation of Our Blessed Lady and the Glory of All the Saints.